2015
DOI: 10.1002/jclp.22161
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Investigation of the Relationship Between Insomnia and Hoarding

Abstract: These findings add to a growing body of literature on insomnia and various forms of psychopathology, as well as research on symptoms related to hoarding. Reducing insomnia symptoms among hoarders may help to reduce hoarding-related behaviors and increase treatment efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
3
8
0
Order By: Relevance
“…However, to date, there has only been one study that investigated the association between sleep and hoarding symptoms at any stage of the lifespan. Raines et al (2015) found that hoarding symptoms, particularly acquiring and difficulty discarding, were associated with increased insomnia in 24 adults with hoarding disorder. Although this study provides initial evidence for the link between hoarding and sleep disturbance, the sample was primarily middle-aged (mean age 42; range 18-63).…”
mentioning
confidence: 92%
“…However, to date, there has only been one study that investigated the association between sleep and hoarding symptoms at any stage of the lifespan. Raines et al (2015) found that hoarding symptoms, particularly acquiring and difficulty discarding, were associated with increased insomnia in 24 adults with hoarding disorder. Although this study provides initial evidence for the link between hoarding and sleep disturbance, the sample was primarily middle-aged (mean age 42; range 18-63).…”
mentioning
confidence: 92%
“…Similarly, we suggest that stress may induce seemingly unrelated behaviors that may become pathological, such as hoarding and OCD. Although such a link has been suggested (Kalanthroff et al 2016; Paterson et al 2013; Raines et al 2015), it is not well studied; our account sheds light on its possible underpinnings.…”
mentioning
confidence: 60%
“…Similarly, we suggest that stress may induce seemingly unrelated behaviors that may become pathological, such as hoarding and OCD. Although such a link has been suggested (Kalanthroff et al 2016;Paterson et al 2013;Raines et al 2015), it is not well studied; our account sheds light on its possible underpinnings.…”
Section: Introductionmentioning
confidence: 75%